Transcriptome Analysis Reveals the Complex Molecular Mechanisms of Brassica napus–Sclerotinia sclerotiorum Interactions - Xu, Binjie; Gong, Xi; Chen, Song; Hu, Maolong; Zhang, Jiefu; Peng, Qi (Frontiers in Plant Science, 2021)
Sclerotinia stem rot (SSR) caused by Sclerotinia sclerotiorum is a devastating disease of many important crops worldwide, including Brassica napus. Although numerous studies on gene expression changes in B. napus and S. sclerotiorum have been performed, knowledge regarding the molecular mechanisms of B. napus–S. sclerotiorum interactions is limited. Here, we revealed changes in gene expression and related pathways in both B. napus and S. sclerotiorum during the SSR infection process using transcriptome analyses. In total, 1,986, 2,217 and 16,079 differentially expressed genes (DEGs) were identified in B. napus at 6-, 24- and 48-h post-inoculation, respectively, whereas 1,511, 1,208 and 2,051 DEGs, respectively, were identified in S. sclerotiorum. The gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses showed that most hormone-signaling pathways in B. napus were enriched, and thus, the hormone contents at four stages were measured. The DEGs and hormone contents revealed that salicylic acid was activated, while the jasmonic acid pathway was repressed at 24-h post-inoculation. Additionally, the expressional patterns of cell wall-degrading enzyme-encoding genes in S. sclerotiorum and hydrolytic enzymes in B. napus were consistent with the SSR infection process. The results contribute to a better understanding of the interactions between B. napus and S. sclerotiorum, and to the development of future preventive measures against SSR.